Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

Mitochondria-related lncRNAs: predicting prognosis, tumor microenvironment and treatment response in lung adenocarcinoma - Qianhui Zhou; Jiali Xiong; Yan Gao; Rong Yi; Yuzhu Xu; Quefei Chen; Lin Wang; Ying Chen (Functional & Integrative Genomics, 2023)
Lung cancer is the most common type of malignant tumor that affects people in China and even across the globe, as it exhibits the highest rates of morbidity and mortality. Lung adenocarcinoma (LUAD) is a type of lung cancer with a very high incidence. The purpose of this study was to identify potential biomarkers that could be used to forecast the prognosis and improve the existing therapy options for treating LUAD. Clinical and RNA sequencing data of LUAD patients were retrieved from the TCGA database, while the mitochondria-associated gene sets were acquired from the MITOMAP database. Thereafter, Pearson correlation analysis was carried out to screen mitochondria-associated lncRNAs. Furthermore, univariate Cox and Lasso regression analyses were used for the initial screening of the target lncRNAs for prognostic lncRNAs before they could be incorporated into a multivariate Cox Hazard ratio model. Then, the clinical data, concordance index, Kaplan–Meier (K-M) curves, and the clinically-relevant subjects that were approved by the Characteristic Curves (ROC) were employed for assessing the model's predictive value. Additionally, the differences in immune-related functions and biological pathway enrichment between high- and low-risk LUAD groups were examined. Nomograms were developed to anticipate the OS rates of the patients within 1-, 3-, and 5 years, and the differences in drug sensitivity and immunological checkpoints were compared. In this study, 2175 mitochondria-associated lncRNAs were screened. Univariate, multivariate, and Lasso Cox regression analyses were carried out to select 13 lncRNAs with an independent prognostic significance, and a prognostic model was developed. The OS analysis of the established prognostic prediction model revealed significant variations between the high- and low-risk patients. The AUC-ROC values after 1, 3, and 5 years were seen to be 0.746, 0.692, and 0.726, respectively. The results suggested that the prognostic model riskscore could be used as an independent prognostic factor that differed from the other clinical characteristics. After analyzing the findings of the study, it was noted that both the risk groups showed significant differences in their immune functioning, immunological checkpoint genes, and drug sensitivity. The prognosis of patients with LUAD could be accurately and independently predicted using a risk prediction model that included 13 mitochondria-associated lncRNAs.

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Method for quantitative extraction of copper hydroxide nanoparticles from farmland soil - Xin-Yuan Li; Yuan Yang; Peng Huang; Ying-Rong Wang; Yu-Lin Nie; Li Zhang; Qiang Wang (Science of The Total Environment, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

OsCIP1, a secreted protein, binds to and stabilizes OsCR4 to promote aleurone layer development, seed germination and early seedling growth in rice - Lin-Lin Yan; Jing Mi; Can-Can Shen; Rong Qian; Jiao Wang; Cui-Xia Pu; Ying Sun (Plant Science, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)